Sui Generis Geographical Indications: Reforming Indonesia’s Intellectual Property Rights for Agricultural Protection - Nurani, Nina; Apriwandi; Hafied Noor Bagja (International Journal of Law and Society, 2025)
Geographical Indications (GI) are agricultural products of high economic value that play an important role in Indonesia's economic development. However, the potential for rights abuse requires protection through adequate Intellectual Property Rights (IPR) regulations. This study aims to analyse international regulations related to GI, evaluate the implementation of GI protection in the Trademark Law for agricultural IPR products in Indonesia, and formulate an effective sui generis IPR regime model to protect agricultural products while supporting national economic development. The study uses a normative juridical approach with a comparative analysis of international and national regulations and a study of IPR and GI theory to formulate a comprehensive regime model. The research findings show that international regulations through Paris, Madrid, Lisbon, and TRIPs provide the basis for GI protection. However, sui generis models such as the European Union or India are more suitable for Indonesia because they can protect cultural diversity and agricultural products while supporting economic development. Second, implementing GI in the Trademark Law in Indonesia is inadequate due to registration disparities, weak quality and reputation maintenance mechanisms, and complaint-based law enforcement, so specific and compelling sui generis regulations are needed. Third, an adequate sui generis IPR regime model is structured around five pillars: simple, participatory digital registration, product quality and reputation standards, collective rights protection, proactive law enforcement through general offences, and integration into national economic development strategies, with philosophical, legal, and sociological foundations. The study concludes that a sui generis IPR regime can enhance agricultural GI protection and support sustainable economic development. The study's limitations relate to the lack of empirical implementation in the field. The research's implications guide regulators in developing a more effective GI regime. The research's originality value lies in integrating international and local perspectives to build a comprehensive sui generis IPR regime for agricultural products in Indonesia.